Structural and electronic properties of two-dimensional multiphase indium selenide crystals - Guilherme Rodrigues Fontenele (2023)
We successfully obtained two indium selenide crystals, with each of the samples having a different proportion of phases and polymorphs. From X-ray diffraction and electron backscattered diffraction measurements, we were able to quantify the proportion of phases in both the volume and surface regions of the crystals. Through microscopy measurements and tunneling spectroscopy, we were able to obtain high-resolution images of the lamellar structures at the nanometer scale, as well as determine the electronic densities of states of InSe and In2Se3, for each phase and polymorph.